INFRARED BOUND TO QUASIBOUND VIBRATION-ROTATION SPECTRUM OF HEH+ AND ITS ISOTOPES - Carrington, A; Kennedy, R; Softley, T; Fournier, P; Richard, E (1983)
The positions and widths of all the bound and rotationally quasibound levels of the ground states of 4HeH-, 4HeD′-3HeH- and 3HeD′ have been calculated using an adiabatic potential. From these theoretical data the positions of bound to quasibound vibration-rotation transitions lying in the range of the carbon dioxide laser 0880 to 1090 cm 1 have been predicted. Infrared predissociation spectroscopy of Doppler-tuned ion beams has been used to determine the positions and widths of many of the resonances. There is excellent agreement between the theoretical predictions and the experimental measurements. © 1983.